2019
DOI: 10.1109/tcomm.2018.2875721
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Constellation Design for the AWGN Channel With Additive Radar Interference

Abstract: Radar and wireless communication coexistence is considered in this paper as a possible solution to face the exploding demand and rising congestion in wireless networks. The transmission medium is modeled as an AWGN channel with additive radar interference. Standard constellations are not optimal in this context and an auto-encoder (AE) is used to design proper constellations and corresponding receiver devices. AE is a powerful tool in neural networks that shares strong similarities with communication systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Considering the simplicity and its popularity, a rate-1/2 convolutional encoder [5,7] 8 is employed in the transmitter along with 4-AM, 4-QAM and irregular 64-ary constellations. (10) with Nc terms for (11).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the simplicity and its popularity, a rate-1/2 convolutional encoder [5,7] 8 is employed in the transmitter along with 4-AM, 4-QAM and irregular 64-ary constellations. (10) with Nc terms for (11).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…While this is true for quasi-regular (QR) cases, many systems are in fact irregular; especially for when the encoders are paired with non-uniformly spaced constellations [10]. For the communication systems suffering from non-cooperative radar interference, the optimal irregular constellations have been proposed in [11] for uncoded scenarios by utilizing deep learning techniques. Interestingly, this can be also observed in the cases where a convolutional encoder used with conventional M -QAM and M -PSK constellations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Wang Li et al proved that some basic reinforcement learning algorithms could be successfully applied to dynamic detection of multiple-input-multiple-output (MIMO) radar with unknown environment and unknown number of targets [23]. Deep learning was used in [24] to discuss channel selection when wideband radar signals coexist with narrowband communication signals in the communication systems.…”
Section: Related Workmentioning
confidence: 99%
“…Owing to these benefits, a number of studies on employing AEs in the physical layer of communication systems has been reported [6,7,8,9,10]. Particularly, the idea of end-to-end learning of communication systems through deep NN-based AEs has been applied to a communication system characterized by an orthogonal frequency division multiplexing with cyclic prefix in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors in [9] develop an AE-based deep learning architecture to model a multiuser single-input multipleoutput communication system. The work in [10] employs an AE to find proper constellations and corresponding receiver devices when a radar systems coexists with interfering wireless systems.…”
Section: Introductionmentioning
confidence: 99%